Dynamic Yet Static: A Boon for High Performance Organizations - Das, Manish (Prabandhan: Indian Journal of Management, 2013)
The present paper is a descriptive research based on secondary data. This paper aims to highlight the practices that make an organization steady, and ensure long-term sustainability of the organization in the challenging marketplace. This paper highlights that to become successful in the long-run, an organization needs to become dynamic in all aspects, including its strategy, product-lines, organizational structure, systems of integration, etc. But some other areas like the organizations' core ideology, value system should remain static. This paper could be a great help for organizations to make themselves sustainable in the long run. Time period of the study : February - July 2012.